Outlaw Motorcycle Clubs and Street Gangs Scheming Legality, Resisting Criminalization (Palgrave Studies in Risk, Crime and Society, 2018)
This edited collection offers in-depth essays on outlaw motorcycle clubs and street gangs. Written by sociologists, anthropologists and criminologists, it asks the question of how the self-proclaimed 'outlaws' integrate into society. While these groups may cultivate a deviant image, these original studies show that we should not let ourselves be deceived by appearances. These 'outlaws' are, paradoxically, well integrated into mainstream society. The essays read the relationship of these groups to the media, law enforcement and society through the lens of their strategies of 'scheming legality' and 'resisting criminalization'. These reveal most strikingly how the knowledge of social codes, norms and mechanisms is put to use by these groups. This groundbreaking volume provides answers to previously understudied questions through well-researched case studies drawn from across Europe and United States. With wide-reaching implications for communities around the world, this exciting collection of essays will be of great interest to academics and governmental institutions as well as students and general readers of anthropology, sociology and criminology. .